The Representation of Staircases in Italian Treatises from the Sixteenth to Eighteenth Centurie (diségno, 2018)
he representation of the staircase is part of the more general theme of architectural drawing. Since ancient times, the designing of the staircase has been worthy of attention, due to both its useful function in overcoming the differences in floors as well as the not immediate mental visualization for articulated spatial solutions; as a consequence, its graphic representation is just as difficult. It has therefore been interesting to investigate this theme by researching it in the Italian treatises that, from the sixteenth to eighteenth centuries, both in literal and graphic form, welcomed and manifested the debate on the designing of staircases.The aforementioned theme was carried out through the analysis of the sources contained in the treaties of Serlio, Palladio, Vignola (commented by Danti), Scamozzi, Guarini and Vittone. Working through the similarities and differences, the ways of describing the staircase have been highlighted and the results placed in the historical-scientific contexts of reference in relation to the geometric coding of the methods of representation. Without prejudice to the common use of drawing as a conceptual conception of visual synthesis, aimed at creativity, knowledge and communication, the reading of the sources has confirmed, on the part of the treatises, the existence of a critical choice of the most appropriate geometric methods of representation (although not yet scientifically codified) or exemptions from them to better describe the spatial qualities of a complex architectural element such as the staircase.
Keywords: Staircase; Treatise; Geometric representation methods; Graphic techniques; Modelling